Study of Biluhuta Seasoning Formulation, Hydratation of Characteristic and Prediction of the Shelf Life Using Moisture Critical Method - Dorkas Sianipar; Sugiono .; Rizal Syarief (Jurnal Teknologi dan Industri Pangan, 2008)
Binthe biluhuta is a native food of Gorontalo, made from mixture of corn, onion, leek, basil, desiccated coconut, chili and fish. The objective of this research was to find the best formulation for binthe biluhuta seasoning and prediction of it’s shelf life. Moisture sorption isotherm derived from the correlation of moisture content data indicated a typical sigmoidal curve implying 3 regions of water adsorption. The water sorption region accounted for three fraction of bound water analyzed using three different mathematical models. The first water fraction ranged 0-3. 148 (%db) and the third fraction ranged 13.438-52970 (%db). The binthe biluhuta seasoning packaged in alumina and stored at 80 and 90% RH, demonstrated the longest shelf life which were equal to 748 and 423 days, respectively. Key word : Binthe biluhuta seasoning, water sorption isothermic, shelf life